2018
DOI: 10.1111/hepr.13051
|View full text |Cite
|
Sign up to set email alerts
|

Relative changes in handgrip strength and skeletal muscle volume in patients with chronic liver disease over a 2‐year observation period

Abstract: Decline in CPS, especially decreasing serum albumin level, showed a significant relationship with muscle function reduction and muscle volume loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
4
10
0
1
Order By: Relevance
“…The level of activity of CLD patients has been reported to be lower compared to normal subjects . Moreover, a decline in Child–Pugh score, especially decreased serum albumin level, was shown to have a significant relationship with decline of handgrip strength and muscle volume . In another study, the efficacy of branched chain amino acids (BCAA), composed of 13.5 g protein, including L‐leucine, L‐isoleucine, and L‐valine (Aminoleban EN; Otsuka Pharmaceutical, Tokyo, Japan) supplementation twice daily without exercise intervention, was found to improve muscle function in LC patients .…”
Section: Discussionmentioning
confidence: 99%
“…The level of activity of CLD patients has been reported to be lower compared to normal subjects . Moreover, a decline in Child–Pugh score, especially decreased serum albumin level, was shown to have a significant relationship with decline of handgrip strength and muscle volume . In another study, the efficacy of branched chain amino acids (BCAA), composed of 13.5 g protein, including L‐leucine, L‐isoleucine, and L‐valine (Aminoleban EN; Otsuka Pharmaceutical, Tokyo, Japan) supplementation twice daily without exercise intervention, was found to improve muscle function in LC patients .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that high WFA + ‐M2BP levels were strongly correlated with the Child–Pugh score . As the Child–Pugh class was an independent predictor linked to skeletal muscle mass decline, it is reasonable to consider that the WFA + ‐M2BP level is a good biomarker and a surrogate for LSMM in patients with liver cirrhosis …”
Section: Discussionmentioning
confidence: 99%
“…Hiraoka et al . reported that decline in the Child–Pugh score showed a significant relationship with muscle function reduction and muscle volume loss . The change in muscle mass is more significant in the severe stages of chronic liver diseases, such as decompensated cirrhosis with complications of hypoalbuminemia, hyposodium, encephalopathy, ascites, and/or hepatic cachexia …”
Section: Introductionmentioning
confidence: 99%
“…Next, we investigated the relationship between sarcopenia‐related indices and changes in liver function. In a previous study, muscle function reduction and muscle volume loss in patients with liver cirrhosis showed a significant relationship with decreasing serum albumin levels . We also previously reported that Japanese patients with NASH whose serum ALT level did not decrease by at least 30% from baseline have a higher risk of disease progression, including both liver fibrosis and NAS .…”
Section: Discussionmentioning
confidence: 64%
“…In a previous study, muscle function reduction and muscle volume loss in patients with liver cirrhosis showed a significant relationship with decreasing serum albumin levels. 28 We also previously reported that Results are the median (range) for quantitative data. †Bold font for P-values indicates <0.05.…”
Section: W E Investigated the Features Of Severalmentioning
confidence: 90%